Data base of Motor learning in human movement science: a bibliometric analysis - Jiménez-Díaz, Judith (2025)
The increase in scientific production in various areas of human movement provides the opportunity to conduct bibliometric studies in motor learning. The aim of the present study was to systematize the information published in motor learning between 2000 and 2024, by means of a bibliometric analysis.  A total of 570 relevant studies on the subject, published between 2000 and 2024, were selected through a search in the Scopus database. An analysis of performance and structure metrics was carried out, considering total publications, number of documents, annual growth rate of published articles, affiliations and most relevant authors, collaboration networks, most cited worldwide, thematic trends, among others. Of the 570 documents analyzed, G. Wulf was identified as the most relevant author, the University of Toronto as the most relevant affiliation, and the United States of America as the country with the highest scientific production. The most cited study aborded the concept of the degrees of freedom problem. In conclusion, this work provides an overview of the scientific production of the subject related to motor learning in the last 25 years.